Production, seasonality and management of chimpanzee food trees in Budongo Forest, Uganda - Tweheyo, Mnason; Babweteera, Fred (African journal of ecology, 2007)
This study monitored the phenology of fruit and leaf of 575 chimpanzee food trees (40 species belonging to fifteen families) in the Budongo Forest Reserve (Uganda) from June 1999 to June 2006. We also monitored the phenology of all fig species in the study area. Fruit quantity varied significantly between species and seasons, with peak during wet season (April–June). The number of tree species in fruit correlated positively with rainfall and was higher during rainy season than dry season. Ficus species had exceptionally high fruit quantities ranging from 400 to 650,000 fruits per tree in a single production period. Leaf flushing peaked during late dry season and early wet season (February–April). Mature leaves were available at all seasons, even when young leaves were emerging. Only Ficus sur, Broussonetia papyrifera and Celtis gomphophylla had fruits throughout the year, and six species did not produce fruits during the study period. Of the twelve species that fruited between 40 and 58 months, three are very important timber species and seven were once killed with arboricides. We conclude that the long-term survival of chimpanzees in tropical forests requires conservation of their food trees.
Keywords: Budongo; Chimpanzee food; Conservation; Human disturbances